Key Factors of Combustion From Kinetics to Gas Dynamics - Rubtsov, Nikolai M. (Springer Aerospace Technology,, 2017)
This book summarizes the main advances in the mechanisms of combustion processes. It focuses on the analysis of kinetic mechanisms of gas combustion processes and experimental investigation into the interrelation of kinetics and gas dynamics in gas combustion. The book is complimentary to the one previously published, The Modes of Gaseous Combustion.